Dietary and genetic evidence for phosphate toxicity accelerating mammalian aging - Ohnishi, Mutsuko (The Federation of American Societies for Experimental Biology, 2010)
Identifying factors that accelerate the aging process can provide important therapeutic targets for slowing down this process. Misregulation of phosphate homeostasis has been noted in various skeletal, cardiac, and renal diseases, but the exact role of phosphate toxicity in mammalian aging is not clearly defined. Phosphate is widely distributed in the body and is involved in cell signaling, energy metabolism, nucleic acid synthesis, and the maintenance of acid-base balance by urinary buffering. In this study, we used an in vivo genetic approach to determine the role of phosphate toxicity in mammalian aging. Klotho-knockout mice (klotho(−)(/)(−)) have a short life span and show numerous physical, biochemical, and morphological features consistent with premature aging, including kyphosis, uncoordinated movement, hypogonadism, infertility, severe skeletal muscle wasting, emphysema, and osteopenia, as well as generalized atrophy of the skin, intestine, thymus, and spleen. Molecular and biochemical analyses suggest that increased renal activity of sodium-phosphate cotransporters (NaPi2a) leads to severe hyperphosphatemia in klotho(−)(/)(−) mice. Genetically reducing serum phosphate levels in klotho(−)(/)(−) mice by generating a NaPi2a and klotho double-knockout (NaPi2a(−)(/)(−)/klotho(−)(/)(−)) strain resulted in amelioration of premature aging-like features. The NaPi2a(−)(/)(−)/klotho(−)(/)(−) double-knockout mice regained reproductive ability, recovered their body weight, reduced their organ atrophy, and suppressed ectopic calcifications, with the resulting effect being prolonged survival. More important, when hyperphosphatemia was induced in NaPi2a(−)(/)(−)/klotho(−)(/)(−) mice by feeding with a high-phosphate diet, premature aging-like features reappeared, clearly suggesting that phosphate toxicity is the main cause of premature aging in klotho(−)(/)(−) mice. The results of our dietary and genetic manipulation studies provide in vivo evidence for phosphate toxicity accelerating the aging process and suggest a novel role for phosphate in mammalian aging.—Ohnishi, M., Razzaque, M. S. Dietary and genetic evidence for phosphate toxicity accelerating mammalian aging.